2018
DOI: 10.1016/j.jbo.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of Ewing sarcoma of bone in India – Evidence from the National Cancer Registry Programme (1982–2011)

Abstract: BackgroundEwing sarcoma is a malignant tumour found mainly in childhood and adolescence. The present study aims at analyzing the data on Ewing sarcoma cases of bone from the National Cancer Registry Programme, India to provide incidence, patterns, and trends in the Indian population.Materials and MethodsThe data of five Population Based Cancer Registries (PBCR) of Bangalore, Mumbai, Chennai, Bhopal and Delhi over 30 years period (1982– 2011) were used to calculate the Age Specific and Age Standardized Incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
6
18
0
Order By: Relevance
“…Table 1 presents that most of the patients were male, white, had a marital status of single/domestic partner, diagnosed in the 2000s or 2010s, treated with surgery, and treated with chemotherapy; these results were consistent with previous research findings [1619]. Although ES has the highest incidence in people under the age of 30 [20], the prognosis is better for those with a younger age of onset and worse for those with a higher age of onset [1]. Similarly, in our nomogram (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Table 1 presents that most of the patients were male, white, had a marital status of single/domestic partner, diagnosed in the 2000s or 2010s, treated with surgery, and treated with chemotherapy; these results were consistent with previous research findings [1619]. Although ES has the highest incidence in people under the age of 30 [20], the prognosis is better for those with a younger age of onset and worse for those with a higher age of onset [1]. Similarly, in our nomogram (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The long-term survival rate of ES for nonmetastatic disease at presentation has improved from 10 to 15% to 60–70% since the early 1990s through the application of multimodality approaches, including surgery, radiotherapy, and neoadjuvant chemotherapy [12, 22, 23]. However, ES exhibits an aggressive behavior that often results in lung metastasis, which is a poor prognostic factor given that only 20% of patients with metastases can survive for a long time [1, 2, 20]. The early identification of high-risk ES patients is helpful in providing adjuvant treatment or trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a devastating, poorly differentiated, and high-grade osteolytic disease threatening human health severely 1,2. Statistically, ES is a rare, aggressive bone neoplasm, and around 2.9 people per million encountered with ES annually worldwide, and predominantly appeared in childhood and adolescence 3,4. ES mainly occurs in bone and surrounding soft tissue characterized by a highly aggressive small round blue cell malignant neoplasm 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Two epidemiologic studies are reported from Iran and India. 5,6 To our knowledge, three studies, all with a retrospective design, have reported on clinical outcomes after multimodality treatment. 7-9…”
Section: Introductionmentioning
confidence: 99%